Cultural Encounters on China’s Ethnic Frontiers - Harrell, Stevan (Studies on ethnic groups in China., 1995)
A civilizing project, as described in this book, is a kind of interaction between peoples, in which one group, the civilizing center, interacts with other groups (the peripheral peoples) in terms of a particular kind of inequality. In this interaction, the inequality between the civilizing center and the peripheral peoples has its ideological basis in the center's claim to a superior degree of civilization, along with a commitment to raise the peripheral peoples' civilization to the level of the center, or at least closer to that level.